DIGITALIZATION IN ELECTRIC POWER SYSTEMS - KAVUN, IVAN; ZAMULKO, ANATOLII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article considers the place of digitalization in modern power systems, the main stages and tasks for the implementation of digitalization processes in the power industry. The role and place of smart systems are determined, as well as their impact on the operation and development of the power supply system as a whole. The main methods for analyzing the state of the system, according to which the research was conducted, are presented, and as a result, a phased implementation of digitalization systems is proposed in accordance with the strategy for the development and restoration of power networks. An analysis of the gaps and deviations between the information and communication technologies and power industries is carried out, the directions of development of the power industry between Ukraine, Europe and the USA are compared, and ways to reduce the gaps between the industries are considered and development directions are outlined. The process of digitalization in the electric power industry is at the development stage, as an integral part of the management process, it ensures the formation of a strategy for the development of the industry. The problem of increasing energy efficiency and energy security, including through digitalization processes, in modern power systems is currently relevant, given the need for rapid action on the part of dispatching, real-time control, development and restoration of power networks, monitoring the state of the power system and new capabilities of digital infrastructure in general. The main goal of the study is to analyze the current state of digitalization in the power system in order to formulate proposals for the implementation of strategies for developing the level of digitalization at power enterprises. The study also aims to assess the advantages and challenges that arise during the implementation of digital technologies in power systems, as well as the prospects for their development in the future.
Keywords: digitalization; management; digitalization processes; intelligent networks; monitoring; digital infrastructure